Controlled release of nutrients from fertilizers through membranes based on natural rubber and coir dust - Karnika de Silva K G; Denawaka Indra; Kariyawasam M G T R; Medhavi Wijesekera D M S (Papers presented at the IRRDB seminar 5-8 November 1996 Sri Lanka p18)
The technique of encapsulating fertilizer for control release of nutrients to the soil is an effective and economical method for dealing with a number of management problems in the field. Prevention of environmental hazards and wastage due to excessive leaching losses of nuterients, possible pilferage and adultaration of fertilizer, reduced labour costs associated with repeated applications are few advantages of using control release of fertilizer over the conventional method of application. The possible utilization of natural rubber and coir dust in fertilizer encapsulation is of great interest to Sri Lanka becasue rubber and coconut are two major agricultural commodities in Sri Lanka. A number of factors controlling the rate of fertilizer release from vulcanized micro cellular natural rubber/coir dust and coir dust and natural rubber latex composite matrices have been investigated. Leaching tests with soil filled columns showed that the rate of nutrients release/volatility release is related to the matrix geometry, and solubility of the fertilizer within the matrix. The leaching tests in water showed that the rate of release is also dependent on the additives in rubber compounding and thickness of the rubber film encapsulating the fertilizer granule. Encapsulated fertilizer so produced thus posses the properties required for regulation of the availability of nutrients. They could reduce leaching losses from agricultural lands thus alleviating the environmental problem and provide a steady prolonged nutrient supply to the plant.
Keywords: Coir dust; Fertilizers; Natural rubber; Nutrient release